PENGARUH ARUS KAS DAN INFLASI TERHADAP LAPORAN PERUBAHAN MODAL (Studi Empiris pada Perusahaan Manufaktur Sub Sektor Food and Beverage yang terdaftar di Bursa Efek Indonesia, Periode 2017-2021). - Wizanasari Wizanasari; Dini Fitrianti; Nani Sriyani (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2021)
This study aims to determine the effect of cash flow and inflation on the statement of changes in capital. This type of research uses associative quantitative, the object of research is food and beverage companies registered with Bursa Efek Indonesia in 2017-2021, using a purposive sampling method in collecting sample data and the type of data used is secondary data. The total number of samples used in this study were 130 out of 26 food and beverage companies registered with the Indonesian Stock Exchange. Data analysis used in this study used panel data regression using the Eviews 12 test tool. The results of this study indicate that together the variables of cash flow and inflation have no effect on reports of changes in capital. Based on the results of the T hypothesis test, it shows cash flow has no effect on reports of changes in capital, and inflation has no effect on reports of changes in capital.